Effects of Dietary Zymosan-A on the Growth Performance and Intestinal Morphology, Digestive Capacity, and Microbial Community in Litopenaeus vannamei - Zheng, Yudong; Hou, Cuihong; Yan, Zhao; Chen, Jian; Wang, Hongming; Tan, Beiping; Zhang, Shuang (Frontiers in Marine Science, 2022)
The effects of dietary zymosan-A on growth performance and the histological structure digestive capacity and microbiota were investigated in Litopenaeus vannamei, an important shrimp species used in aquaculture. L. vannamei (initial body weight = 0.41 ± 0.05 g) were fed diets with zymosan-A supplemented at doses of 0 (Z0, control), 1 (Z1), 5 (Z5), 25 (Z25), 125 (Z125) or 625 (Z625) mg/kg for 8 weeks. The results show that doses of 25 and 125 mg/kg significantly increased the final body weight, weight gain rate (WGR) and specific growth rate (SGR), and significantly decreased the feed conversion rate compared with controls (P < 0.05). According to the analyses of WGR and SGR, the optimum dietary zymosan-A level is 308.56 or 300.00 mg/kg, respectively. Compared with controls, the intestinal villus height was significantly increased by zymosan-A addition at doses ≥ 25 mg/kg (P < 0.05). Obvious upregulation of trypsin and amylase activities were observed in all zymosan-A-added groups, while lipase activity was significantly increased in Groups Z125 and Z625 (P < 0.05). Consistently, the gene expressions of trypsin and lipase were significantly higher in Group Z125, while amylase gene expression was significantly increased in all zymosan-A-added groups (P < 0.05). Analysis of intestinal microbiota showed significant differences in alpha diversity between Group Z125 and controls. Treated groups showed altered intestinal bacterial community structures and compositions at the phylum, family and genus levels, with statistical differences observed in the relative abundances of some dominant species. Tax4fun predictions of the microbiota indicated that multiple intestinal functions were significantly altered in all zymosan-A-added groups except Z1. Among them, the functions related to transport and catabolism, substance dependence, cardiovascular disease, and signalling molecules and interactions were obviously increased by zymosan-A addition of different levels. In conclusion, dietary supplementation with the optimum amount of zymosan-A can improve growth and intestinal function in L. vannamei, which will be valuable in aquaculture.